Prevalence and genotype distribution of high‐risk human papillomavirus infection among women with cervical cytological abnormalities in Chongqing, China, 2014–2020. Issue 12 (28th October 2021) - Luo, Qinli; Lang, Lin; Han, Na; Liang, Ling; Shen, Lianjun; Zhang, Haiyan
Abstract: Background: Persistent infection with high‐risk human papillomavirus (HR‐HPV) is the main leading cause of cervical precancerous lesions and cervical cancer. This study aims to explore the epidemiological characteristics of HR‐HPV genotypes and their correlation with the ThinPrep cytological test (TCT) results among women in Chongqing, in China. Methods: In this retrospective study, cervical exfoliations of 14, 548 women who visited Chongqing university cancer hospital were collected for detecting HR‐HPV genotypes and TCT. Results: Overall, the rate of HR‐HPV infection was 14.26%. The three most common HR‐HPV genotypes are HPV52 (4.39%), HPV58 (2.21%), and HPV16 (1.94%). In this study, the positive rate of cervical TCT was 4.54%. Atypical squamous cells of undetermined significance (ASC‐US), atypical squamous cells that could not exclude high‐grade squamous intraepithelial lesion (ASU‐H), low‐grade squamous intraepithelial lesions (LSIL), high‐grade squamous intraepithelial lesions (HSIL), and atypical glandular cells of undetermined significance (AGC) were 2.99%, 0.20%, 0.92%, 0.29%, and 0.14%, respectively. Among the several types of cytological lesions, the HR‐HPV infection rates of ASC‐US, ASC‐H, LSIL, HSIL, and (AGC) were 24.82%, 41.38%, 64.18%, 95.24%, and 23.81%, respectively. Conclusions: HPV52, HPV 58, and HPV16 are the most common infection subtypes in Chongqing. When implementing HPV vaccine programs in Chongqing, HPV58 and HPV52 should be attached importance as HPV16 and HPV18.